Karyotype and chromosomal characteristics of rDNA of Cobitisstrumicae Karaman, 1955 (Teleostei, Cobitidae) from Lake Volvi, Greece - Hnátková, Eva; Triantaphyllidis, Costas; Ozouf-Costaz, Catherine; Lukáš Choleva; Majtánová, Zuzana; Bohlen, Joerg; Ráb, Petr (Comparative cytogenetics, 2018)
The karyotype of Greek cobitid fish Cobitisstrumicae Karaman, 1955, from Lake Volvi, Greece, a representative of one of its two major intraspecific phylogenetic lineages, was analysed by means of sequential Giemsa-staining, C-banding, silver-staining, CMA3 fluorescence banding and also by in situ hybridization (FISH) with rDNA probe. The diploid chromosome number was 2n = 50, karyotype composed of 10 pairs of metacentric to submetacentric and 15 pairs of subtelocentric to acrocentric chromosomes. The nucleolus organizer regions (NORs) as revealed by Ag- and CMA3 staining and FISH were situated in the telomeric region of the fourth submetacentric chromosome pair. The chromosomes contained very low content of C-positive heterochromatin. No heteromorphic sex chromosomes were detected. This first karyotype report for any species of lineage Bicanestrinia Băcescu, 1962 shows a simple karyotype dominated by acrocentric chromosomes and possessing single NOR-bearing chromosome pair. Cytotaxonomic implications of this finding for the taxonomy of the genus Cobitis Linnaeus, 1758 are further discussed.
Keywords: chromosome banding; rDNA; NOR phenotype; FISH; cytotaxonomy of Cobitis loaches